A review of the Australian skate genus Pavoraja Whitley (Rajiformes: Arhynchobatidae) - Last, Peter R.; Mallick, Stephen; Yearsley, Gordon K. (Zootaxa, 2008)
The Australian endemic skate genus Pavoraja Whitley, which contains six species including two valid nominal species (P. alleni and P. nitida) and four new species (P. arenaria sp. nov., P. mosaica sp. nov., P. pseudonitida sp. nov. and P. umbrosa sp. nov.), is redefined based on additional material. Members of the group occur primarily on the outer continental shelf and upper slope in both temperate and tropical Australian seas. The species are strongly partitioned geographically with smallto medium-scale ranges. Pavoraja arenaria is known to have a broad southern distribution but none is widespread in the Australian region. Only two species pairs, P. nitida and P. arenaria (off southern Australia), and P. mosaica and P. pseudonitida (off northeastern Australia), are known to be sympatric. New information is provided for the two nominal taxa, and the four new species are formally described and figured. Skeletal characteristics are described and illustrated, and a key to species is provided. Members of the genus differ primarily in colour pattern, squamation, morphometrics, meristics, and anatomical structure. The relationships of the genus Pavoraja to other arhynchobatid skates are discussed briefly.